2021
DOI: 10.1021/acs.jmedchem.1c00795
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Modified Antimicrobial Peptides from the N-Terminal Domain of Human RNase 3 Show Exceptional Serum Stability

Abstract: Multidrug resistance against conventional antibiotics poses an important threat to human health. In this context, antimicrobial peptides (AMPs) have been extensively studied for their antibacterial activity and promising results have been shown so far. However, AMPs tend to be rather vulnerable to protease degradation, which offsets their therapeutic appeal. Here, we demonstrate how replacing functional residues in the antimicrobial region of human RNase 3also named eosinophil cationic proteinby non-natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Based on a target proteolysis study in serum, peptide analogues were synthesized with either all D-AA, Arg to Orn substitutions or blockage of peptide bond cleavage by D-AA introduction. Additionally, based on the previous analysis of the proteolysis digestion products [ 28 ], ECPep-2D-Orn was selected. ECPep-2D-Orn is the Orn-peptide analogue, which showed the highest half-life in serum and incorporates a D-AA at position 2 ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on a target proteolysis study in serum, peptide analogues were synthesized with either all D-AA, Arg to Orn substitutions or blockage of peptide bond cleavage by D-AA introduction. Additionally, based on the previous analysis of the proteolysis digestion products [ 28 ], ECPep-2D-Orn was selected. ECPep-2D-Orn is the Orn-peptide analogue, which showed the highest half-life in serum and incorporates a D-AA at position 2 ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Structural analysis in aqueous solution and in the presence of lipid dodecyl phosphocholine (DPC) micelles was previously assessed by NMR [ 28 ]. NMR indicated that the 30mer L-reference peptide adopts in aqueous solution a defined helix from residues 5 to 13 and tends to helical structuration within the 16–27 stretch.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations